The first helicoid sea slug: 3D microanatomy of Helicohedyle dikiki n. gen., n. sp. (Panpulmonata: Acochlidiida) from Guam. (12th October 2017) - Drainas, Konstantina; Carlson, Clayton H; Jörger, Katharina M; Schrödl, Michael; Neusser, Timea P
Abstract: Large parts of the discovered diversity of sea slugs are still undescribed, despite their potential contribution to a better understanding of the evolution of the group. Here, we describe an enigmatic tiny sea slug that was discovered in the 1970s on subtidal reef flats on Guam (Mariana Islands, Indo-West Pacific). The slug presents a long, coiled visceral sac, unique within the highly diverse body plans of sea slugs, which are usually characterized by different degrees of external body symmetry, linked to the reduction of the shell. Its initial assignment to the order Acochlidiida is confirmed by our 3D-microanatomical study based on a histological section series. Helicohedyle dikiki n. gen., n. sp. shows a number of putative plesiomorphic characters such as a simple excretory system—including a sac-like kidney combined with a short nephroduct—and an androdiaulic, hermaphroditic reproductive system, which bears an unarmed copulatory organ. Based on external morphology and microanatomical data it can be assigned to the Hedylopsacea and shows affinities both with marine and brackish Pseudunelidae, and also with limnic Tantulidae. We discuss the different potential scenarios of the evolution of a helicoid visceral sac as a secondary adaptation to the benthic marine lifestyle vs its interpretation as a plesiomorphic character from a coiled and shell-bearing ancestor, predating the transition to the interstices of sandy habitats associated with (progenetic) modifications in body plans.